Kemandirian Pengelolaan Mutasi Pns Antar Daerah Dalam Era Otonomi Daerah - Sri Riris Sugiyarti, Beni Supartono Putro & (Transformasi, 2012)
AbstractThe alteration of regional goverment management in the regional autonomy era issignificantly brings a change in the implimentation regional personnel management, includinginter-regional placement of civil servant. In fact the emergence of this tedency in the intraregionalmutation of goverment officials is interrelated with regional ego as the impact ofregional autonomy euphoria. This research used deskriptive qualitatif method, which is expectedto be able to present variables and the sign that was achieved for secondary data and primarydata through in dept interview and observation in the research location (in BKD City ofSurakarta).Keyword : independency, mutation management, and autonomy era